Developing a Transformative E-module with Reflective Video Tasks on Waste Management to Enhance Environmental Sensitivity - Aqil, Deden Ibnu; Abbas, Hafid; Astra, I Made; Vhalery, Rendika (Asian Journal of Interdisciplinary Research, 2026)
This study seeks to create a transformational project-based E-module featuring reflective video activities centered on local waste management challenges to foster environmental awareness among high school students in Depok, Indonesia. The module was tested with 10th grade students in a senior high school in Depok using the ADDIE model and a mixed-method approach. The e-module called "e-ling" has both asynchronous and synchronous functionalities and uses real-world waste management concerns as project-based activities. To see if the module was possible and useful, researchers used expert validation sheets, environmental sensitivity scales (before and after tests), and questionnaires for students and teachers. Expert evaluation in pedagogy, media, content, and language got an average score of 84.28%. Student and teacher answers showed that the material was very good (96% and 90%, respectively). Effectiveness testing showed that students' environmental sensitivity got a lot better, with an N-Gain score of 0.53 (moderate) and an average posttest score of 300 (high). These results indicate that the E-modul module is both viable and efficacious in improving students' environmental awareness, particularly with urban waste management issues in Depok.